The Interpretation of Signs on Projection Art of Veil of An Artist and A Fictional Dialogue - Kong, Hannah Nyuk Fun; Imelda Ann Achin; Addley Bromeo Bianus (Penerbit UMS, 2022)
The form of communication of new media art serves as a vital link between the world of art and the society. The scenario for the advancements of new media art in our country is inadequate in respect of the intellectualism aspects of studies and the knowledge of projection art. As part of this study, projection art in Malaysia will be analysed to see how artists employ technology and visual art semiotics to convey their ideas to audiences effectively. This paper discusses the projection artworks produced by Hasnul Jamal Saidon titled Veil of an Artist and A Fictional Dialogue. The semiotics approaches which involve in constructing the content analysis semiology and in-depth interviews were utilised to analyse the projection artwork by Hasnul Jamal Saidon. Furthermore, this study aims to discover the value of message that embedded in the projection artworks of Hasnul as well as to interpret the signs and meanings included in each piece of art. According to the research, projection artwork of Hasnul demonstrates the new media and its always changing, intricate ways in which individuals express and interpret in different perspective of the value of the subject, and ideologies of nature, as well as social morality, and conventional standards. Study finding shows that artworks may effectively transmit the intended messages of the artist as well as themes and issues that they addressed regardless of the date or place in which they were produced.